2018
DOI: 10.1002/14651858.cd013152
|View full text |Cite
|
Sign up to set email alerts
|

Health-improving interventions for obtaining employment in unemployed job seekers

Abstract: BackgroundUnemployment is associated with decreased health which may be a reason or a consequence of becoming unemployed. Decreased health can inhibit re-employment. ObjectivesTo assess the e ectiveness of health-improving interventions for obtaining employment in unemployed job seekers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…There is also a lack of synthesised evidence on how health-related interventions could reduce obesity and increase employment. While some systematic reviews [ 30 , 31 ] have suggested a beneficial effect of interventions in reducing obesity and increasing employment, the evidence has been inconclusive. It is also not clear which contexts or mechanisms are required for the successful implementation and effective uptake of such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a lack of synthesised evidence on how health-related interventions could reduce obesity and increase employment. While some systematic reviews [ 30 , 31 ] have suggested a beneficial effect of interventions in reducing obesity and increasing employment, the evidence has been inconclusive. It is also not clear which contexts or mechanisms are required for the successful implementation and effective uptake of such interventions.…”
Section: Introductionmentioning
confidence: 99%